The little house - Burton, Virginia Lee (Boston : Houghton Mifflin Co., 1988)
A country house is unhappy when the city, with all its buildings and traffic, grows up around her.
Sound cassette compatible for manual and automatic operation.
85071
Keywords: Dwellings -- Fiction; City and town life -- Fiction